Why don't firms lobby? How information shapes the market for lobbying services - Benjamin C. K. Egerod; Lasse Aaskoven (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2024)
Why do some firms lobby consistently while others never lobby at all? We argue that most firms lack information about the market for lobbying services. This implies that even when there are large returns associated with a political presence, most firms will not lobby. We present comprehensive evidence from US publicly traded firms supporting this argument. First, using a natural experiment, we show that only firms that already have a political presence use lobbying to deal with political shocks. Second, firms start lobbying when they receive an influx of information about political strategy among other firms. Third, the information effect is present among firms that can rely on trade associations for lobbying needs. Our results suggest that lack of information keeps firms from lobbying that would benefit from it. This has large consequences for the input available to decision-makers.
Keywords: 330